GE_GERICHTE P/8363/2019 vom 17. März 2021 - GE Cour de justice (2021)
ENLÈVEMENT DE MINEUR(INFRACTION);VIOLATION DU DEVOIR D'ASSISTANCE OU D'ÉDUCATION;EXEMPTION DE PEINE | CP.220; CP.52; CP.219; CPP.382.al1; CP.3.al1